An Experimental Examination of Two Exchange Institutions - Plott, C. R.; Smith, V. L. (Review of Economic Studies, 1978)
Charles R. Plott, Vernon L. Smith; An Experimental Examination of Two Exchange Institutions, The Review of Economic Studies, Volume 45, Issue 1, 1 February 1978